Evaluating Server Technologies for Internet and Intranet Applications - Peter Varhol (computer technology ressearch corp, 1997)
Excutive summary; State-of-th-Art Technology; Web server requirements; Considering theoperating system; Considering the operating system; the sun solution; Intel's alternative; What about the mainframe; Other web server platforms...